Acute effects of 3,4-dichloroaniline on biomarkers and spleen histology of the common goby Pomatoschistus microps - Monteiro, M.
The aromatic amine 3,4-dichloroaniline (DCA) is a model environmental contaminant, precursor for synthesis and degradation product of several herbicides, which is commonly found in European estuarine ecosystems. In this work, the possibility of using biochemical and histological markers to assess sub-lethal effects of DCA in natural populations of Pomatoschistus microps juveniles was investigated. Alterations on the activities of the enzymes acetylcholinesterase (AChE), lactate dehydrogenase (LDH) and glutathione S-transferase (GST) and histological alterations on spleen were investigated after 96 h of exposure to sublethal concentrations of DCA (0.50-1.49 mg/l). At the concentrations tested, DCA had no effect on AChE activity. LDH and GST activities were significant altered in treated animals when compared to control groups. As already described for mammals, DCA induced splenic histological alterations in P. microps, including expansion of red pulp and deposition of hemosiderin granules in a concentration-dependent manner. This suggests that DCA is a xenobiotic of concern in estuaries receiving agricultural effluents. (c) 2005 Elsevier Ltd. All rights reserved.